2004
DOI: 10.1016/s1471-5953(03)00066-0
|View full text |Cite
|
Sign up to set email alerts
|

Determining the value of simulation in nurse education: study design and initial results

Abstract: Nowadays simulation is taking an important place in training and education of healthcare professionals. The University of Hertfordshire is carrying out a study which aims to determine the effect of realistic scenario-based simulation on nursing students' competence and confidence. This project is sponsored by the British Heart Foundation and takes place in the Hertfordshire Intensive Care and Emergency Simulation Centre (HICESC), a simulated three adult beds Intensive Care Unit. The simulation platform used is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
91
0
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(109 citation statements)
references
References 16 publications
8
91
0
10
Order By: Relevance
“…Among the sub-area scores of clinical competence, basic nursing performance score were the highest, followed by patient education, and psychosocial nursing. This result matched the findings of Alinier, Hunt and Gordon (2004) that simulation-based education helped to improve skills, and also matched the findings of Hur, Choi, Jung, Kang, & Kim (2012) that simulation-based practice improved the performance skills of nursing students. The students' basic nursing performance improved because the simulation-based education included practice with taking vital signs, performing intravenous injections, and providing oxygen therapy in its first session, which preceded the actual simulation in the second session.…”
Section: Discussionsupporting
confidence: 85%
“…Among the sub-area scores of clinical competence, basic nursing performance score were the highest, followed by patient education, and psychosocial nursing. This result matched the findings of Alinier, Hunt and Gordon (2004) that simulation-based education helped to improve skills, and also matched the findings of Hur, Choi, Jung, Kang, & Kim (2012) that simulation-based practice improved the performance skills of nursing students. The students' basic nursing performance improved because the simulation-based education included practice with taking vital signs, performing intravenous injections, and providing oxygen therapy in its first session, which preceded the actual simulation in the second session.…”
Section: Discussionsupporting
confidence: 85%
“…[3][4][5] Simulation has gained credibility as an effective teaching technique for undergraduate nursing students, and there is evidence to support the increase of knowledge, skills, and critical thinking, and the ability to recognize a deteriorating patient using clinical simulation. [6][7][8] Studies also indicate that with simulation students have increased critical thinking skills. [9][10][11] Despite common use and evidence to support its effectiveness, the use of simulation in health professions education remains controversial.…”
Section: Simulationmentioning
confidence: 99%
“…[1][2][3][4] High-fidelity simulation has become increasingly popular in pharmacy education in the United States after the Accreditation Council for Pharmacy Education indicated that colleges and schools could include simulation as part of introductory pharmacy practice experiences in doctor of pharmacy (PharmD) degree programs. 5 Many pharmacy programs have included simulation training only at certain stages in their curricula, while others have successfully incorporated it throughout the curriculum.…”
Section: Introductionmentioning
confidence: 99%